Synergistic Doping and Intercalation: Realizing Deep Phase Modulation on MoS2 Arrays for High‐Efficiency Hydrogen Evolution Reaction. (24th September 2019) - Deng, Shengjue; Luo, Mi; Ai, Changzhi; Zhang, Yan; Liu, Bo; Huang, Lei; Jiang, Zheng; Zhang, Qinghua; Gu, Lin; Lin, Shiwei; Wang, Xiuli; Yu, Lei; et al.
Abstract: A synergistic N doping plus PO4 3− intercalation strategy is used to induce high conversion (ca. 41 %) of 2H‐MoS2 into 1T‐MoS2, which is much higher than single N doping (ca. 28 %) or single PO4 3− intercalation (ca. 10 %). A scattering mechanism is proposed to illustrate the synergistic phase transformation from the 2H to the 1T phase, which was confirmed by synchrotron radiation and spherical aberration TEM. To further enhance reaction kinetics, the designed (N, PO4 3− )‐MoS2 nanosheets are combined with conductive vertical graphene (VG) skeleton forming binder‐free arrays for high‐efficiency hydrogen evolution reaction (HER). Owing to the decreased band gap, lower d‐band center, and smaller hydrogen adsorption/desorption energy, the designed (N, PO4 3− )‐MoS2 /VG electrode shows excellent HER performance with a lower Tafel slope and overpotential than N‐MoS2 /VG, PO4 3− ‐MoS2 /VG counterparts, and other Mo‐base catalysts in the literature. Abstract : N‐Dotierung plus PO4 3− ‐Interkalation wurden genutzt, um eine hohe Umwandlungsrate (41 %) von 2H‐MoS2 zu 1T‐MoS2 zu induzieren – viel höher als bei alleiniger N‐Dotierung oder PO4 3− ‐Interkalation (28 % bzw. 10 %). Für die Umwandlung von der 2H‐Phase in die 1T‐Phase wird ein Streuungsmechanismus vorgeschlagen, der durch Synchrotronstudien und TEM mit sphärischer Aberration bestätigt wird.